Profitable Horizontal Mergers without Cost Advantages: The Role of Internal Organization, Information, and Market Structure - Steffen Huck; Kai A. Konrad; Wieland Müller (Center for Economic Studies and ifo Institute (CESifo), 2001)
Merged firms are typically rather complex organizations. Accordingly, merger has a more profound effect on the structure of a market than simply reducing the number of competitors. We show that this may render horizontal mergers profitable and welfare-improving even if costs are linear. The driving force behind these results, which help to reconcile theory with various empirical findings, is the assumption that information about output decisions flows more freely within a merged firm.
Keywords: 330; Merger; internal organizational structure; information; timing; market structure